Effect of antiretroviral therapy to liver function of people living with HIV/AIDS patients in West Papua - Mirna Widiyanti; Setyo Adiningsih; Evi Iriani Natalia; Dedi Ananta Purba (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background : Antiretroviral (ARV) therapy is one of the efforts to combat HIV/AIDS in Indonesia, especially West Papua. One of the side effects using ARV is impaired liver function in People Living with HIV/AIDS (PLWHA). ARV therapy evaluation to liver disorders can be seen from the Serum Glutamic Oxaloacetic Transaminase (SGOT)/ Serum Glutamic Pyruvic Transaminase (SGPT) level.Objective : To find out the effect of ARV Fixed Dosed Combination (FDC) to liver function of PLWHA patients in West Papua.Methods : A cross-sectional study, involving 110 respondents who were PLWHA patients receiving ARV at Voluntary Counselling and Testing (VCT) service of hospital in Manokwari, Sorong, and Fak-fak. Laboratory tests was used to examine the liver function. Other variable data were obtained from medical records. The Fisher Exact Test with a significance level of <0.05 was used to determine the effect of ARV to liver function.Results : Respondents had no liver problems with normal SGOT and SGPT values, i.e. 72,7% and 76.4%, respectively. While, the rest had mild and moderate toxicity. Respondent experiencing moderate toxicity was 2 patients who regularly took FDC in Sorong.Conclussion : The FDC using in ARV therapy did not significantly influence the increase of SGOT and SGPT on PLWHA patients in West Papua.